Sustainability Disclosure in Supporting Good Governance Practices in the Public Sector - Rizky, Muhammad; Prastya, Heru; Ni’mah, Zakiyatun; Firmansyah, Amrie (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
The practice of issuing sustainability reports, which has been widely adopted by private parties, does not appear to be a big concern for the public sector, particularly government organizations in Indonesia. This research aims to examine the feasibility of issuing sustainability reports for government agencies as part of adopting good governance exercises. The scoping review approach is used in this study to collect information from references related to sustainability disclosure and then evaluate situations relevant to the aims and scope of research connected to governance in the public sector. This study concludes that sustainability disclosure is driven by the role of management from internal organizations, motivational references such as those in the private sector, and a commitment to reducing emissions and implementing sustainable governance. However, there exist obstacles in the form of undeveloped public sector sustainability reporting standards. This research is expected to contribute to Indonesian government agencies, KSAP, and the larger community developing policies and standards for sustainability disclosure in the public sector.